The right of local government employees to expungement of disciplinary offences processed digitally in Jordanian and Qatari legislation - Jehad D. Aljazi (Faculty of Law, University of Muhammadiyah Malang, 2025)
This paper examines a right that has emerged due to the activities performed by users on the internet, specifically the right to digital expungement of disciplinary offences committed by Municipal Employees and the penalties imposed on them, and its relationship with public service. The issue addressed is whether the legislative provisions in Qatar and Jordan are sufficient to safeguard and preserve this right. This paper demonstrates all the legal provisions related to the right to digital expungement of disciplinary offences and applies an analytical comparative approach between the Jordanian and Qatari legislation. In conclusion, with several findings and recommendations, this study highlights the existence of a relationship between the right to digital expungement and the statute of limitations for disciplinary offences and penalties due to the similarity in their legal effects. The study recommends reversing the recent amendment to the Civil Service Regulation No. 34 of 2024, which deleted the provisions related to the statute of limitations for disciplinary offences and the expungement of disciplinary penalties after a certain period defined by the relevant stipulations. It suggests adding these provisions to the new Human Resources Management Regulation No. (33) Of 2024.